Analysis of the Effect of Interest Rates, Inflation Rates and Exchange Rates on PT Astra Agro Lestari Tbk's Syari'ah Share Prices Listed on the Jakarta Islamic Index (JII) 2015 - 2021 - Trisna Asih; Muhammad Ridho (Jurnal Rekognisi Akuntansi, 2023)
This study aims to determine several external factors including interest rates, inflation, rupiah exchange rates and world oil prices in influencing Islamic stock prices at PT Astra Agro Lestari Tbk which are listed on the Jakarta Islamic Index (JII) for 2015 – 2021. This research uses 84 monthly financial reports at PT Astra Agro Lestari Tbk for 2015-2021 as a samples, and saturated sampling as the sampling method. This research uses multiple regression analysis in the IBM SPSS Statistics 25 program as The analytical method. The results of this research showed that the interest rate variable did not have a significant effect, the inflation variable had a positive and significant effect, the rupiah exchange rate variable had a negative and significant effect, while world oil prices had no significant effect on Islamic stock prices at PT Astra Agro Lestari Tbk in 2015-2021